2019
DOI: 10.23937/2474-3658/1510102
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Re-Treatment Cases and Factors Associated with Unfavourable Outcome at the Fann University Hospital of Dakar, Senegal between 2011 and 2016: A Follow-Up Study

Abstract: Introduction: The aim of our study was to describe the socio-demographic, clinical, therapeutic and evolutionary characteristics of patients admitted to tuberculosis re-treatment and managed at the The Infectious and Tropical Diseases Department (SMIT) screening and tuberculosis treatment center (TTC), to determine the factors associated with unfavourable outcome Methodology: This is a descriptive and analytical retrospective cross sectional study covering all tuberculosis re-treatment cases monitored in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…This is in line with many other studies, including one conducted in Eritrea that showed the same results. 29 This finding relates to the higher mortality rate in HIV patients, which is a result of their lower immune function, and the higher lost-to-follow-up rate, which is a result of the higher stigma associated with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with many other studies, including one conducted in Eritrea that showed the same results. 29 This finding relates to the higher mortality rate in HIV patients, which is a result of their lower immune function, and the higher lost-to-follow-up rate, which is a result of the higher stigma associated with HIV.…”
Section: Discussionmentioning
confidence: 99%